2013
DOI: 10.1159/000350004
|View full text |Cite
|
Sign up to set email alerts
|

ASURA (PHB2) Interacts with Scc1 through Chromatin

Abstract: Sister chromatid cohesion mediated by the cohesin complex is essential for faithful chromosome segregation. Previously we reported that PHB2 (prohibitin2/ASURA), a multifunctional protein, has a role in sister chromatid cohesion. Nevertheless, how ASURA is involved in sister chromatid cohesion still remains unclear. The present co-immunoprecipitation analysis reveals that ASURA interacts with cohesin subunit Scc1 in vivo. We show that ASURA associates with chromatin in a similar manner as Scc1 throughout the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Furthermore, we observed that upon PHB2 silencing, RD cells showed a stable tendency of cell cycle G1 phase arrest. These results are consistent with the study by Equilibrina et al ., which demonstrated that PHB2 was required for G1/S progression since the number of cells undergoing extended G1 phase increased significantly under the PHB2 knockdown condition 33 . We also found that PHB2 silencing could induce apoptosis in a small proportion of RD cells.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, we observed that upon PHB2 silencing, RD cells showed a stable tendency of cell cycle G1 phase arrest. These results are consistent with the study by Equilibrina et al ., which demonstrated that PHB2 was required for G1/S progression since the number of cells undergoing extended G1 phase increased significantly under the PHB2 knockdown condition 33 . We also found that PHB2 silencing could induce apoptosis in a small proportion of RD cells.…”
Section: Discussionmentioning
confidence: 90%